Strategic positioning of the ‘ERATOSTHENES Research Centre’ in the Eastern Mediterranean and Middle East region: ERATOSTHENES Remote Sensing Super Site - Mamouri, Rodanthi-Elisavet; Ansmann, Albert; Nisantzi, Argyro; Bühl, Johannes; Seifert, Patric; Wandinger, Ulla; Hadjimitsis, Diofantos G. (My University, 2018)
The vision of the ERATOSTHENES Research Centre (ERC) of the Cyprus University of Technology (CUT) is to become a Centre of Excellence for Earth Surveillance and Space-Based Monitoring of the Environment in the framework of the EU H2020 Teaming project EXCELSIOR. In this contribution we report on recent progress regarding the buildup of a permanent, state-of-the-art atmospheric remote sensing station at Limassol, Cyprus, in the Eastern Mediterranean and Middle East (EMME) region. This effort is performed in close cooperation with the Leibniz Institute for Tropospheric Research (TROPOS), Leipzig Germany. We already operate the fully established PollyNet-CLOUDNET supersite LACROS in Cyprus for a period of 1 year as part of Phase 1 of the EXCELSIOR project. The Cy-CARE (Cyprus Cloud Aerosol and pRecipitation Experiment) has been designed by TROPOS and was implemented at CUT in October 2016 with main focus on the lidar/radar-based study of aerosol-cloud-precipitation processes in a region of high pollution, strong dust outbreaks, and expected strong changes in climate conditions during the next decades. The EXCELSIOR team consists of CUT (acting as the coordinator), the German Aerospace Centre (DLR), the Institute for Astronomy and Astrophysics Space Applications and Remote Sensing of the National Observatory of Athens (NOA), TROPOS, and the Cyprus’ Department of Electronic Communications of the Ministry of Transport, Communications and Works (DEC-MTCW). This team will work together to significantly improve the research capabilities of CUT and the network infrastructure in Cyprus with respect to atmospheric, environmental and Earth science by means of active remote sensing from ground and passive remote sensing from space.
Keywords: Climate change; Dust; Remote sensing